Nuclear factor I enhances adenovirus DNA replication by increasing the stability of a preinitiation complex. - Mul, Y M (1992)
Nuclear factor I (NFI) or its isolated DNA-binding domain (NFI-BD) enhances initiation of adenovirus DNA replication up to 50-fold at low concentrations of the precursor terminal protein-DNA polymerase (pTP-pol) complex. Both in solution and when bound to DNA, NFI-BD can form a complex with pTP-pol. To investigate the mechanism of enhancement by NFI, we determined the stability of a functional preinitiation complex formed in vitro between pTP-pol and the origin. Challenge experiments with a distinguishable template containing an identical origin revealed that in the absence of NFI, this preinitiation complex was very sensitive to competition for pTP-pol. Addition of NFI-BD increased the half-life of the complex at least 10-fold and led to the formation of a template-committed preinitiation complex. In agreement with this, binding of pTP-pol to origin DNA in band-shift assays was enhanced by NFI. By DNase I footprinting we show that the specificity of binding as well as induction of structural changes in origin DNA by pTP-pol are increased by NFI. These results indicate that NFI, by binding and positioning pTP-pol, stabilizes the complex between pTP-pol and the core origin, and thus enhances initiation of DNA replication.